A Mathematical Demonstration of the Viability of Profit/Loss Sharing as a Debt Alternative in Presence of Market Frictions. (December 2018) - Wolf, Franziska; Nabin, Munirul H.; Bhattacharya, Sukanto
We posit a simple mathematical model to show that a profit-and-loss sharing contract can be formed between a capital seeker and capital provider as a potential alternative to institutional debt financing. The major methodological tool used is that of Nash bargaining ; utilising the matching theory proposition of Pissarides (2000). Our posited model demonstrates that a 'match' between a capital seeker and a capital provider can occur even in the presence of embedded market frictions arising out of information asymmetries as are especially rife in the emerging markets. This is an important result especially for marginal borrowers in emerging economies and we present supporting empirical evidence that indicates profit-and-loss sharing being increasingly seen as an effective alternative financing to long-term borrowing. JEL Classification: C78, D53, G23